A Meta‐Analysis of HIV Postexposure Prophylaxis Among Sexually Assaulted Patients in the United States [RETRACTED]. (January 2018) - Scannell, Meredith; Kim, Tiffany; Guthrie, Barbara J.
Abstract : N/A: Sexual assault (SA) is a major public health problem that leaves patients at risk for HIV. The gold standard of medical treatment for SA patients includes prophylactic treatment to prevent HIV. A meta‐analysis was conducted and examined the rates of nonoccupational postexposure prophylaxis (n‐PEP) offered to, accepted, and completed by SA patients who presented to emergency departments in the United States. Four points of data were analyzed: (a) SA patients who met the criteria and were offered n‐PEP, (b) SA patients who were offered n‐PEP and accepted the medication, (c) SA patients who accepted n‐PEP treatment and completed at least one follow‐up appointment, and (d) SA patients who completed the entire course of n‐PEP. Results of the meta‐analysis indicated that approximately half of the patients who were offered n‐PEP accepted the medication. However, only 25.7% of SA patients who accepted n‐PEP completed the full course.